Using Anime to Enhance Learning Motivation and Japanese Listening Skills - Wisniawati, Wisniawati; Rasiban, Linna Meilia; Dewanty, Via Luviana (Universitas Muhammadiyah Mataram, 2022)
Teaching and learning activities Japanese listening skills need the motivation to support learning. However, learning motivation sometimes fluctuates, and the use of learning methods and media is not precise. This study aims to analyze the level of motivation and listening ability of students after using anime learning media. This study used a qualitative method with a note-taking technique and the sample used in this study is 16 students Department of Japanese Language in Bandung State West Java. The results of the data showed that the use of anime in listening comprehension learning was able to increase learning motivation and listening skills. This is evidenced by the activities carried out by students when learning takes place and the value of assignments obtained by students has increased.